ERRATUM TO: CAREGIVERS’ EXPERIENCE IN MEETING SELF-CARE NEEDS OF ADOLESCENTS WITH AUTISM SPECTRUM DISORDER: A QUALITATIVE STUDY - Lilis Lestari; Elisabeth S Herini; Indria Laksmi Gamayanti (Belitung Raya Foundation, Indonesia, 2020)
After publication of the article (Lestari et al., 2017), it has been brought to our attention that the wrong title was used on initial publication. The correct title of this article is “Caregivers’ experience in meeting self-care needs of adolescents with autism spectrum disorder: A qualitative study”. The original version of the article has been updated to reflect this. In addition, the reference format in this article has also been updated. The corrected article can be seen in the following link https://doi.org/10.33546/bnj.123 The publisher apologizes for the errors.